2010
DOI: 10.1007/s10546-010-9534-8
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Flow and Pollutant Transport in Urban Street Canyons with Ground Heating

Abstract: Our study employed large-eddy simulation (LES) based on a one-equation subgrid-scale model to investigate the flow field and pollutant dispersion characteristics inside urban street canyons. Unstable thermal stratification was produced by heating the ground of the street canyon. Using the Boussinesq approximation, thermal buoyancy forces were taken into account in both the Navier-Stokes equations and the transport equation for subgrid-scale turbulent kinetic energy (TKE). The LESs were validated against experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 37 publications
10
50
0
1
Order By: Relevance
“…Li et al [54,55] have performed LES studies of flow and pollutant dispersion in street canyons of h/b = 0.5, 1, and 2 with ground heating (Ri ranging from −0.5 to −2.9), where "ground heating" is the term used for heating or cooling of the air near the ground by heat transfer to or from the ground. Their results showed that the ground heating significantly enhanced the mean flow, turbulence, and turbulent pollutant flux inside street canyons, but weakened the shear layer at the roof level.…”
Section: Flow Turbulence and Scalar Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [54,55] have performed LES studies of flow and pollutant dispersion in street canyons of h/b = 0.5, 1, and 2 with ground heating (Ri ranging from −0.5 to −2.9), where "ground heating" is the term used for heating or cooling of the air near the ground by heat transfer to or from the ground. Their results showed that the ground heating significantly enhanced the mean flow, turbulence, and turbulent pollutant flux inside street canyons, but weakened the shear layer at the roof level.…”
Section: Flow Turbulence and Scalar Fieldmentioning
confidence: 99%
“…On the other hand, the profile of turbulent heat/pollutant flux can vary depending on the location of the source. For the cases with flux/pollutant source at the ground level, the flux values usually have two maxima: near the source and at the roof level (see [54,55]). However, above the roof level, the transport processes of these fluxes are quite similar under near-neutral conditions [65].…”
Section: Scalar Transfermentioning
confidence: 99%
“…A two-dimensional (2D) street canyon is a simplification of an actual urban geometry. Numerous studies have focused on the impact of building characteristics (such as building heights, the shape roof of building, and the density of the building group) on the diffusion of pollutants in idealized and modeling urban street canyons (Li et al, 2008;Huang et al, 2009;Li et al, 2010;Buccolieri et al, 2011;Scargiali et al, 2011;Hang et al, 2012;Addepalli and Pardyjak, 2013;Scungio, 2013;Huang et al, 2015). Scungio et al (2015a) have used the detached eddy simulation to study the turbulent flow in isolated street canyons of different aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2010Li et al ( , 2014 have investigated the flow field and pollutant dispersion characteristics inside urban street canyons with ground heating at different Richardson (Ri) numbers. Increasing ground temperature substantially enhanced the mean flow, turbulence, and pollutant flux inside the street canyons, but weakened the shear at the roof level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al (2008a) studied momentum and pollutant transport in deep street canyons of aspect ratio 3 and 5, which are commonly found in dense compact cities across the world. Apart from isothermal conditions, the number of large-eddy simulations investigating the effects of unstable stratification on the microscale climate in street canyons is increasing (Cai 2009;Li et al 2009Li et al , 2010Park and Baik 2009). …”
Section: Introductionmentioning
confidence: 99%